1989
DOI: 10.1099/00221287-135-4-767
|View full text |Cite
|
Sign up to set email alerts
|

Nucleotide Sequence of the Bacillus licheniformis Homologue of the Sporulation Locus spoIIA of Bacillus subtilis

Abstract: The spoIIA locus of Bacillus licheniformis was cloned into the phage vector 4105J9; selection was based on the ability of the clone to complement mutations in both the first and the last of the spoIIA genes of B. subtilis. The B . licheniformis DNA was subcloned into M13 and sequenced; it includes three genes of identical lengths to those of B. subtilis. The average interspecies difference in nucleotide sequence is 24%; C occurs at the third position of codons 55% more often in the B. fichenvormis than in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

1991
1991
1996
1996

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…The DNA sequences of PCR products were determined by the automated DNA sequencing service provided by the Department of Molecular Medicine, Kings College, University of London, London, United Kingdom (an ABI model 373A DNA sequencer is used to determine sequences). The sequencing primer used, 5Ј-CGATCATGGAAAATTTCATG GATG-3Ј, was complementary to a region approximately 100 bases upstream of the proposed recombination junction, corresponding to bases 943 to 966 in the previously published sequence (33).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The DNA sequences of PCR products were determined by the automated DNA sequencing service provided by the Department of Molecular Medicine, Kings College, University of London, London, United Kingdom (an ABI model 373A DNA sequencer is used to determine sequences). The sequencing primer used, 5Ј-CGATCATGGAAAATTTCATG GATG-3Ј, was complementary to a region approximately 100 bases upstream of the proposed recombination junction, corresponding to bases 943 to 966 in the previously published sequence (33).…”
Section: Methodsmentioning
confidence: 99%
“…Our understanding of the genetics of sporulation in Bacillus subtilis is now at an advanced stage (9,15), and, on the basis of the sporulation genes of B. licheniformis which have been well characterized (14,16,17,33), it seems likely that this close relative of B. subtilis has a similar, if not identical, developmental pathway. The first morphological change observed during the sporulation process is the synthesis of an asymmetric septum at stage II.…”
mentioning
confidence: 99%
“…We then examined this upstream region. Yudkin et al (1989) isolated a clone from B. licheniformis that contained the spoZZA region. Sequencing showed that the third gene of the region was succeeded by a sequence that resembled a strong transcription terminator.…”
Section: Resultsmentioning
confidence: 99%
“…subtilis lies another sporulation locus, spo VA. There are several reasons for believing that in B. subtilis spoVA is transcribed separately from spoIIA : first, experiments with integrational plasmid vectors suggest that the two loci belong to different transcriptional units ; secondly, the sequence immediately downstream of spoIIA includes what appears to be a terminator of transcription (Wu et al, 1989;Yudkin et al, 1989); thirdly, results of experiments with fusions of spoVA to lac2 show that spoVA is expressed much later in sporulation than spoIIA (Errington & Mandelstam, 1986); fourthly, expression of spoVA, unlike that of spoIIA, must take place in, and is confined to, the prespore compartment (Errington & Mandelstam, 1986 ;Gholamhoseinian & Piggot, 1989); fifthly, the size of spoIIA mRNA estimated from Northern blots agrees with that predicted for a tricistronic spoIIA message (Savva & Mandelstam, 1986). We now describe experiments whose results have identified the startpoint of transcription of spoVA, and show that the spoVA promoter, which is identical in sequence in B. subtilis and B. lichenformis, resembles promoters that are known to be recognized by RNA polymerase containing aG.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation